Pengaruh Lokasi, Harga dan Fasilitas terhadap Keputusan Sewa Kamar Kost Mahasiswa Fakultas Ekonomi Universitas Samudra - Iriyani; Suri Amilia (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2019)
ABSTRACT The objective of the research was to ﬁnd out the location, price and facilities of rental room decisions of the students Fakultas Ekonomi Universitas Samudra. Data analysis method using multiple linear regression, with multiple linear regression analysis equation in research are: Y = 2.597 + 0.184X1 + 0.184X2 + 0.044X3. The value of Adjusted R Square obtained by 0,17 or 17,0% indicates the ability of the location, price and facilities of rental room decisions of the students Fakultas Ekonomi Universitas Samudra, while the remaining 83.0% is influenced by other variables that are not in accordance with this study such as research, security and other relationships etc. From the results of trials on the location of the lease significant to the rental room decision and the hypothesis accepted, the price does not matter significantly to the rental room decision and the hypothesis rejected, and the facilities are not significant to the rental room decision and the hypothesis rejected. From the trial results prove the location, price and simultaneous facilities significantly influence room rental decisions the students Fakultas Ekonomi Universitas Samudra and the hypothesis accepted.